Kábel TV Gyönk
a compilation, folk dance festival of cooperatives, excursion of the pensioners' club in the Danube curve, exhibition of Lajos Ágh Ajkeling in Budapest, who was born in Gyönk, excursion of the pensioners' club in Sopron, German guest, folk dance, fire brigade's brass band, folk dance group and band in Greece, five schoolchildren in a (former East) German holiday camp, Greek folk dance group in Hungary, museum, wine, Eger